Enhancement of thermographic images as tool for structural analysis in earthquake engineering. (March 2015) - Cluni, F.; Costarelli, D.; Minotti, A.M.; Vinti, G.
Abstract: In this paper, we present an application of a reconstruction method to thermographic images employed to analyze the response of a masonry structure under seismic actions. At first the theory of linear multivariate sampling Kantorovich operators is presented. By means of the above operators, we are able to reconstruct images taken from thermographic survey of masonry walls, and enhance their quality. Digital image processing of reconstructed images allows us to identify the mutual arrangement of the blocks (made of stones and/or bricks) and mortar joints inside the wall portion analyzed, and therefore the texture of the masonry. Subsequently, the texture has been used to estimate the equivalent elastic properties of the masonry by means of homogenization techniques. Finally a real-world case-study is analyzed, taking into account the mechanical properties estimated from reconstructed thermographic images and evaluating the structural response in terms of modal analysis. Abstract : Highlights: We use thermographic images to assess the structural characteristics of a building. We reconstruct and enhance images using multivariate sampling Kantorovich operators. We estimate the mechanical characteristics of masonry using reconstructed images. We show improvement in the estimation of dynamic response using reconstructed images.